Order reduction of linear time-invariant systems using Eigen permutation and Jaya algorithm. Issue 9 (2nd September 2019) - Gupta, Akhilesh K.; Kumar, Deepak; Samuel, Paulson
ABSTRACT: This article presents a new mixed method for order reduction of higher order linear time-invariant systems using Eigen permutation and the Jaya optimization algorithm. The Jaya algorithm is an algorithm-specific parameter-free optimization which requires tuning of standard control parameters only. On the other hand, the Eigen permutation retains the dominant poles of the original system with simultaneous cluster formation of the remaining real and complex poles. The numerator and the denominator polynomials of the reduced order model are determined using the Jaya optimization and Eigen permutation approaches, respectively. The proposed method results in a stable reduced order model for a stable higher order system. The effectiveness of the proposed method is validated using numerical examples of single-input–single-output and multiple-input–multiple-output systems. Furthermore, the results are compared with well-known existing techniques available in the literature.